2003
DOI: 10.1080/10915810305090
|View full text |Cite
|
Sign up to set email alerts
|

Fire Ant Venom Alkaloid, Isosolenopsin A, a Potent and Selective Inhibitor of Neuronal Nitric Oxide Synthase

Abstract: Massive, multiple fire ant, Solenopsis invicta, stings are often treated aggressively, particularly in the elderly, despite limited evidence of systemic toxicity due to the venom. Over 95% of the S. invicta venom is composed of piperidine alkaloid components, whose toxicity, if any, is unknown. To assess a possible pharmacological basis for systemic toxicity, an alkaloid-rich, protein-free methanol extract of the venom from whole ants was assayed for inhibitory activity on the following nitric oxide synthase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 42 publications
0
33
0
3
Order By: Relevance
“…Ant venom is composed of a complex mixture of chemicals such as proteins, enzymes, biogenic amines, peptides, hydrocarbons, formic acid and alkaloids (Davies et al, 2004;Kem et al, 2004;Yi et al, 2003). All these compounds are produced by the venom gland, which consists of two free cylindrical elongated and convoluted tubes, linked to a venom reservoir (Ortiz and Mathias, 2006).…”
Section: Ant Venom Functionsmentioning
confidence: 98%
“…Ant venom is composed of a complex mixture of chemicals such as proteins, enzymes, biogenic amines, peptides, hydrocarbons, formic acid and alkaloids (Davies et al, 2004;Kem et al, 2004;Yi et al, 2003). All these compounds are produced by the venom gland, which consists of two free cylindrical elongated and convoluted tubes, linked to a venom reservoir (Ortiz and Mathias, 2006).…”
Section: Ant Venom Functionsmentioning
confidence: 98%
“…Consequently, stings of red imported fire ants represent a significant human health hazard (Stafford, 1996;Vinson, 1997;Kemp et al, 2000). Yi et al (2003) indicated that three major NOS (nitric oxide synthase) isoforms (nNOS, eNOS and iNOS) should be inhibited by S. invicta venom alkaloids, and isosolenopsin A (cis-2-methyl-6-n-undecylpiperidine), an alkaloid component of fire ant venom, was synthesized and tested for inhibitory activity against three NOS isoforms. The results showed that activities of nNOS and eNOS isoforms were over 95 % inhibited with 1000 mM of isosolenopsin A, whereas the enzyme activity for iNOS was inhibited by only about 20 % with the same concentration of isosolenopsin A (Yi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Yi et al (2003) indicated that three major NOS (nitric oxide synthase) isoforms (nNOS, eNOS and iNOS) should be inhibited by S. invicta venom alkaloids, and isosolenopsin A (cis-2-methyl-6-n-undecylpiperidine), an alkaloid component of fire ant venom, was synthesized and tested for inhibitory activity against three NOS isoforms. The results showed that activities of nNOS and eNOS isoforms were over 95 % inhibited with 1000 mM of isosolenopsin A, whereas the enzyme activity for iNOS was inhibited by only about 20 % with the same concentration of isosolenopsin A (Yi et al, 2003). Both solenopsin A (trans-2-methyl-6-n-undecylpiperidine) and isosolenopsin A cause seizures and depress cardiovascular functions in rats (Howell et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…neuronal nitric oxide synthase) involved in cellular signalling and neuronal excitability. 22,37,[89][90][91] Electrophysiological recordings have been instrumental in determining the varied pharmacological effects of toxins and venom components on cellular function, and have provided fundamental insight into ion channel structure and function. For example, nAChRs were isolated by virtue of high affinity binding of a-bungarotoxin from snake venom, [92][93][94] whereas the pore region of the K + channel was rst dened through electrophysiological characterisation of mutants with altered binding of charybdotoxin from scorpion venom.…”
Section: Single Cell Electrophysiological Recordings To Assess the Efmentioning
confidence: 99%